Hall effect and electrical studies of chlorophyll-polypyrrole thin films deposited on indium-tin oxide - Norlaily Abdul Rashid (Terengganu : Universiti Malaysia Terengganu, 2012)
A relatively novel technology, polymer solar cells have been under investigate in universities, national laboratories and several companies around the world. In comparison to the silicon-based devices, polymer solar cells are lightweight (which is important for small autonomous sensors), disposable, inexpensive to fabricate, flexible, customizable on the molecular level, and environmental friendly. The setback of the solar cell is its energy conversion factor. One way to increase the efficiency is to fabricate materials which have high mobility values and high concentration of the charge carrier. The present work is considered crucial and beneficial in industries and in research field.